The Insidence of Sexual Violence and Domestic Violence Before the COVID-19 Pandemic and During the COVID-19 Pandemic at POLRI Hospital East Jakarta Year 2017-2021 Based on the Visum et Repertum Results and the Review Ascording to the Islamic Perspective - Annisa Fitri Ramadhany; Ferryal Basbeth; Firman Arifandi (Junior Medical Journal, 2022)
Sexual violence is a degrading act against a person's body without consent that causes physical, psychological and sexual suffering. Meanwhile, acts of domestic violence include physical, psychological, sexual and economic violence. During the COVID-19 pandemic, individual social space is limited and creates economic pressure which has implications for cases of sexual violence and domestic violence in Indonesia. This study aims to determine the incidence of unnatural deaths before and during the COVID-19 pandemic. This study used a descriptive method with a retrospective study design using medical records from 805 victims of sexual violence and 520 victims of domestic violence. The population of this study were victims of sexual violence and domestic violence (2017-2021) who were examined at the POLRI Hospital East Jakarta according to inclusion criteria. The results showed that the frequency of victims of sexual violence cases was 805 victims and domestic violence was 520 victims. The frequency of victims in cases of sexual violence occurred the most in 2020 or during the COVID-19 pandemic as many as 236 victims. Based on gender, the most cases were women as many as 222 victims occurred in 2020. The age range of the most sexual violence cases occurred in 2020 with an age range of 12-16 years as many as 99 victims. The highest frequency of victims in domestic violence cases occurred in 2020 or during the COVID-19 pandemic as many as 161 victims. Based on gender, the most women as many as 133 victims occurred in 2020. The age range of the most domestic violence cases occurred in 2021 with an age range of 26-35 as many as 55 victims. It can be concluded that the incidence of sexual violence and domestic violence during the COVID-19 pandemic was higher than before the COVID-19 pandemic.